Intake, bioavailability, and absorption of iron in infants aged 6 to 36 months: an observational study in a Brazilian Well Child Clinic - Faleiros, Francisca Teresa Veneziano [UNESP]; da Silva, Valéria Nóbrega [UNESP]; de Assis Carvalho, Mary [UNESP]; Machado, Nilton Carlos [UNESP] (Springer Nature, 2016)
Background: Preventing the development of iron deficiency anemia during infancy requires the appropriate complementary foods with high energy, nutrient density, and adequate iron content, as well as high nutrient bioavailability. We aimed to evaluate iron intake, bioavailability, and absorption from foods, in healthy infants and toddlers at a Well Child Clinic. Methods: This observational, cross-sectional, descriptive study evaluated 96 consecutive infants and toddlers, 6 to 12 months of age (group I) and 13 to 36 months of age (group II) that were brought for regular pediatric visits and introduced to complementary foods. Quantitative 24-h dietary recalls were obtained, and iron intakes quantified for lunch and dinner. Iron bioavailability and absorption were calculated and analyzed by Monsen’s and FAO/WHO’s methods according to enhancing factors: meat, poultry, and fish (MPF) and vitamin C. Results: There were no significant differences in demographic, clinical, and anthropometric variables between groups. Vitamin C intake was not different between groups, but MPF was significantly lower in group I. The proportion of children with recommended RDA iron intake was lower (p < 0.05) in group I (16 %) than that in group II (47 %). Group I had lesser MPF intake and iron absorption and a higher proportion of children with low bioavailability in lunch and dinner when compared to group II (p < 0.05). Conclusions: Inclusion of low-cost meat, especially chicken meat and vitamin C-rich foods, at the same meal, both in lunch and dinner, would be of particular advantage to ensure an adequate intake of bioavailable iron during complementary feeding.
Keywords: Absorption; Bioavailability; Diet; Infant; Iron